2019
DOI: 10.1182/blood-2019-128475
|View full text |Cite
|
Sign up to set email alerts
|

Smart Start: Rituximab, Lenalidomide, and Ibrutinib Alone and in Combination with Standard Chemotherapy for Patients with Newly Diagnosed Diffuse Large B-Cell Lymphoma: Final Phase II Results

Abstract: Background: Diffuse Large B-cell Lymphoma (DLBCL), the most common lymphoid cancer, is classified by the cell of origin into the germinal and non-germinal center (non-GCB) subtypes. The non-GCB subtype is associated with inferior outcomes with standard therapies, but the BTK inhibitor ibrutinib (I) and immunomodulatory agent lenalidomide (L) have moderate activity as single agents and result in synthetic lethality when combined in non-GCB DLBCL models (Yang, Cancer Cell 2012). When added to chemotherapy for DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In this study, 60 patients with non‐GCB DLBCL were enrolled, and results in 58 evaluable patients showed an ORR of 100% (CR 95%, PR 5%) with a 1‐year PFS of 92.5% at the 16 months follow‐up. Notably, one patient had a fatal fungal infection (CNS aspergillosis) attributed to concomitant use of high dose corticosteroids, leading to the prohibition of corticosteroids during the RLI only cycles with no further fungal infections identified 39 …”
Section: Upfront Therapymentioning
confidence: 99%
“…In this study, 60 patients with non‐GCB DLBCL were enrolled, and results in 58 evaluable patients showed an ORR of 100% (CR 95%, PR 5%) with a 1‐year PFS of 92.5% at the 16 months follow‐up. Notably, one patient had a fatal fungal infection (CNS aspergillosis) attributed to concomitant use of high dose corticosteroids, leading to the prohibition of corticosteroids during the RLI only cycles with no further fungal infections identified 39 …”
Section: Upfront Therapymentioning
confidence: 99%
“…Moreover, promising and durable activity was observed for triplet ibrutinib, rituximab, and 10–25 mg lenalidomide (IR2 regimen) in r/r DLBCL, particularly in non-GCB DLBCL (ORR: 65% vs. 29%; median DoR: 15.9 vs. 8.8 months, for non-GCB vs. GCB, respectively) [ 119 ]. In SMART START trial, the same triplet combination with 25 mg lenalidomide as a leading-in regimen in the first-line setting for non-GCB DLBCL gave impressive results, with an ORR and CR rate of 86% and 36%, respectively, after two cycles of IR2 treatment [ 120 ]. Prolongation of IR2 use and reduction in chemotherapy cycles are needed in future exploration, especially for those relatively unfit patients.…”
Section: Molecular Pathway Inhibitorsmentioning
confidence: 99%
“…158 A recent phase II study of ibrutinib and lenalidomide, in combination with R-CHOP, showed promising results. 159 Other inhibitors of the proximal components of the BCR pathway, such as fostamatinib (syk inhibitor) and enzastaurin (PCKβ inhibitor) have shown limited effect in DLBCL; 160,161 on the other hand, JNJ-67856633, a MALT-1 inhibitor, showed efficacy in preclinical studies and is currently investigated in a phase I trial in DLBCL patients (NCT03900598). 162 Activation of the PI3K pathway represents an important oncogenic event in most DLBCL cases.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%